Plan de negocios para la creación de un centro de alto rendimiento para ciclistas amateur en la ciudad de Quito - Fierro Proaño, Erick Ramiro (2020)
Sports in Ecuador have gone through a metamorphosis in recent years. It went from being considered a hobby, to become a biological need because of human need for movement, being recommended by health experts for almost the entire population. Thus, cycling, due to its complexity and completeness, has become one of the fastest growing sports in the country. Thanks to this, at present, the State has promoted laws and reforms, which favor both the athletes who emerge from this discipline, and the private sector for supporting them. Taking into account these factors and the need in the market, the project for the creation of a high-performance center for amateur cyclists in the city of Quito is presented. Whose objective is to improve the health of cyclists resident in Quito, to whom we offer three different services that require the medical, technical and physical field. For this, a marketing plan is projected in which the strategy and methods to achieve the stated objectives are specified. In addition, a 60-month financial projection was made, which resulted in positive values, which verified the viability of the project.